Modeling the Energy Harvested by an RF Energy Harvesting System Using Gamma Processes. (28th April 2019) - Castro, Inma T.; Landesa, Luis; Serna, Alberto
Abstract : In an Energy Harvesting system (EHS) the gamma process is used to model the electromagnetic energy received from radiofrequency (RF) radiation. The stochastic characterization of the harvested energy as a continuous-time stochastic process, namely, gamma process, is obtained from the Nakagami-m fading model, which describes the signal reception in a large amount of types of radiofrequency channels. Using the gamma process, some performance measures of the EHS system are obtained. Also, a transmission policy subject to different fading conditions is considered.